Clinical and epidemiological profile of cases of poisoning brought to a tertiary care centre located in a rural border district of South Kerala (Indian Journal of Forensic Medicine & Toxicology, 2025)
Background: Poisoning remains a critical public health issue in India, with varying epidemiological and clinical characteristics across different regions. Identifying demographic trends, types of poisons consumed and their clinical presentations are crucial for improving prevention and treatment strategies. This study aims to analyze the general characteristics, clinical manifestations, trends and patterns of poisoning cases in a hospital setting.Methods: A retrospective study of 247 patients brought with a definite history of poisoning and treated for at least 48 hours, during the last 10 years was conducted. Data on patient demographics, type of poison consumed, manner of poisoning, clinical features, factors precipitating consumption of poisonous substances, duration of hospital stay, outcome and complications developed were collected from medical records. Descriptive statistical analysis was done to assess patterns and trends of poisoning.Conclusion: The study revealed that poisoning incidents were predominantly reported among males and individuals aged 25-50 years, with a significant proportion being linked to suicidal intent. Drug related poisoning was the most common and alcoholism was a prevalent comorbidity. These findings underline the need for targeted interventions, improved mental health and community support and effective management of poisoning cases to reduce the burden of this malady in the population.
Keywords: Poisoning, clinical profile, suicidal poisoning, organophosphates, toxicology, retrospective analysis